2022
DOI: 10.3390/biomedicines10112762
|View full text |Cite
|
Sign up to set email alerts
|

Diversities in the Gut Microbial Patterns in Patients with Atherosclerotic Cardiovascular Diseases and Certain Heart Failure Phenotypes

Abstract: To continue progress in the treatment of cardiovascular disease, there is a need to improve the overall understanding of the processes that contribute to the pathogenesis of cardiovascular disease (CVD). Exploring the role of gut microbiota in various heart diseases is a topic of great interest since it is not so easy to find such reliable connections despite the fact that microbiota undoubtedly affect all body systems. The present study was conducted to investigate the composition of gut microbiota in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…Other results were obtained by Drapkina and his team [14]. They examined the composition of the gut microbiota in three groups of patients: those with atherosclerotic cardiovascular disease, HF patients with reduced ejection fraction (HFrEF), and HFpEF patients.…”
Section: Richness and Diversity Of Gut Microbiota (Alpha Diversity) A...mentioning
confidence: 98%
See 1 more Smart Citation
“…Other results were obtained by Drapkina and his team [14]. They examined the composition of the gut microbiota in three groups of patients: those with atherosclerotic cardiovascular disease, HF patients with reduced ejection fraction (HFrEF), and HFpEF patients.…”
Section: Richness and Diversity Of Gut Microbiota (Alpha Diversity) A...mentioning
confidence: 98%
“…The intestinal microbiota produces diverse metabolites that exhibit effects on the body, both positive and negative [14]. More research attempts to identify the relationship between these metabolites and specific diseases and even use them as potential predictive factors.…”
Section: Introductionmentioning
confidence: 99%
“…Анализ КМ проводился с помощью методов ПЦР-РВ и секвенирования нового поколения (next generation sequencing, NGS). Проведение экспериментов подробно описано в предыдущей статье [6].…”
Section: материал и методыunclassified
“…The microbiota, and their genes, called the microbiome, has been studied intensely through the past years using novel metagenomics, metatranscriptomics, and metabolomics approaches [73]. Fecal microbiota composition and diversity may be evaluated by three methods: living organisms are determined using bacterial cultures, total DNA taxonomic composition is estimated by next generation sequencing of rRNA gene and quantitative assessment of several taxa is performed using specific quantitative polymerase chain reaction (qPCR) [94]. Landmark microbiome-host genome-wide association studies have identified many SNPs associated with gut microbiota [95].…”
Section: Microbiota: Definitions and Functionsmentioning
confidence: 99%
“…Some microbial components are more represented in in the blood, fecal and plaque samples of patients with cardiovascular risk factors or disease [3,94,95,[114][115][116][117][118][119][120].…”
Section: Western Diet Microbiome and Cardiovascular Diseasesmentioning
confidence: 99%